Perbandingan Kesetaraan Hak Pekerja Perempuan dalam Ruang Lingkup Ketenagakerjaan di Indonesia dan Amerika Serikat - Natasya Radha; Aloysius Uwiyono (Publikasi Indonesia, 2023)
The polemic regarding the equality of women workers seems to be an issue that will never end for discussion. The equality of women workers is a form of recognition of the rights of women workers who need to improve their welfare. Indonesia and the United States of course have their own problems and efforts in dealing with the issue of equal rights for women workers. The purpose of this research is to find out the comparison of conditions and developments in the level of equality of rights of women workers in Indonesia and the United States. The results of the study show that the equality of women workers in Indonesia is more dominated by discrimination of the wage gap, while the United States is still engaged in the struggle to eradicate gender discrimination caused by race, skin type and the place where women workers come from.